Effects of selective forebrain noradrenaline loss on behavioral inhibition in the rat. - Mason, S; Iversen, S (1977)
Virtually total depletion of cortical and hippocampal noradrenaline by stereotaxic injection of 6-hydroxydopamine into the fibers of the dorsal noradrenergic bundle produced no impairment in acquisition learning of a runway response for food reward. Extinction of this response, once learned, was markedly slower in the treated group than in controls, the treated animals perseverating in rapid running to the goal box even with no food present there. Similarly, no impairment was found on acquisition of a continuously reinforced lever-pressing response for food. Extinction of this response, however, was again slower in the treated group. Subsequent acquisition of a successive light-dark discrimination task was also slower in the treated group, with these animals perseverating in responding to the negative stimulus. Although selective forebrain noradrenaline loss does not impair the acquisition of appetitive responses, the suppression of responses in the absence of reward is impeded. A parallel is drawn with those effects found classically after surgical lesion to the hippocampus.